Recovery and Improvement of Cocoa Production With the Use of Nutrients from Chitosan-Tonnage Blending Ash. Issue 1 (1st November 2022) - Suherman,; Sabang, Sri Mulyani; Rahmawati, Sitti; Supriadi,
Abstract: Cocoa is one of the plantation crops that provide a high economic contribution to Central Sulawesi Province in particular and Indonesia in general and be the main income for local farmers. Cocoa is a non-oil and gas export commodity with high demand, therefore the government has determined cocoa as a strategic commodity that needs to be increased in productivity and developed as a source of income for Indonesia and State of Sulawesi. The purpose of this study was to make chitosan-tonnage blending in the composition of 80%-90% and to characterize it and its optimal ratio to restore soil nutrients, so the plants can be resistant to pests and Vascular Streak Dieback (VSD). Furthermore, cocoa fruit were powdered to become as raw material for bispic products. Chitosan come from chitin, with shrimp as raw material, tonnage was cocoa pods which have been hit by black fruit borers. Cocoa plants come from a less productive farmer area of 1 Ha, located in Rantekala Village, Gumbasa District, SigiBiromaru Regency. The results of this study revealed that of the cocoa fruit diameter which is given nutrient elements from chitosan-blending ashesat fruit age ± 6 weeks was 23 cm, compared with the cocoa fruit diameter that only given ZA / NPK fertilizer was 14.5 cm at the age of 7 weeks. The length of the cocoa fruit that was given nutrient elements from chitosan-blending ash blending at ± 6 weeks fruit age was 28 cm, while the cocoa fruit that was given ZA fertilizer only was 21 cm in length at 7 weeks. The production of cocoa beans which were given nutrient elements with chitosan-tonnage blending ashes increased by 60% compared to those that were only given ZA fertilizer. The conclusion from this study was the nutrients from chitosan-tonnage blending ash could be increase the size of the cocoa fruit around 37% for diameters and 27% for lengths greater than those given with ZA fertilizer.